Developing Water Resources Within and Without Borders: Egypt’s Road to Achieve Sustainable Development - Hossam Moghazy (Renewable Energy and Sustainable Development)
Egypt is currently facing a significant challenge to strike a balance between the increasing demand of water and its available amounts; hence, the Egyptian Ministry of Water Resources and Irrigation has laid down a water policy that takes into consideration the present challenges and the future changes. To counter these challenges, this water policy is based on eight pivotal points as follows:  Developing water resources within and without borders in cooperation with the River Nile basin countries;  Rationing water usage to make the best use of water resources;  Improving water quality so as to protect the environment and citizens’ general health;  Supporting national projects and integrated development along with promoting investment and exports;  Consolidating and rehabilitating facilities and water-lifting stations to guarantee optimal usage control, develop irrigation condition, and upgrade irrigation and sewage networks;  Protecting coasts and facilities from climate changes and torrents threats; and  Adopting the concept of water resources integrated management. The Ministry of Water Resources and Irrigation strongly believes that developing water resources both within and without borders is Egypt’s road to achieve sustainable development, and therefore the Ministry adopts all scientific and executive measures to reach these goals for the welfare of Egyptian citizens. I would like to thank the Renewable Energy and Sustainable Development Journal issued by the Academy Publishing Center of the Arab Academy for Science, Technology and Maritime Transport and to wish its board every success. May God Almighty guide us towards the welfare of our beloved Egypt. Prof. Hossam Moghazy Minister of Water Resources and Irrigation